Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Prestasi Belajar PPKn Peserta Didik Kelas IX.3 SMP Negeri 4 Praya Timur - Raihun Raihun (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2019)
This study was aimed to know the improvement of PPKn learning achievement of the grade IX.3 students in SMP Negeri 4 Praya Timur by using Discovery Learning model. This research was a classroom action research with 21 students, consisting of 10 female students and 11 male students as the research subjects. This research was conducted in two cycles consisting of planning, action, observation, and reflection, where each cycle was carried out in three meetings. Based on the results of the study, it was obtained that in pretest stage there were 61.90% of students were declared unfinished and 38.10% of students declared complete with the highest score of 87. The number of students who reached the KKM target in the first cycle pretest was as many as 8 out of 21 students. After implementing the Discovery Learning model in the first cycle, there were 38.10% of students who did not complete, and 61.90% of students who were declared complete with the highest score of 91. The number of students who met the KKM standard was 13 out of 21 participants. However, after the implementation of the second cycle, the number of students in the posttest who completed as much as 90.48% and those who were declared incomplete was 9.52% with the highest value of 100. The number of students who received grades above the KKM standard was 19 out of 21 students. Thus, the researcher can conclude that the Discovery Learning learning model applied has a positive influence on students learning achievement.